2010
DOI: 10.1002/acp.1750
|View full text |Cite
|
Sign up to set email alerts
|

The effect of short duration heart rate variability (HRV) biofeedback on cognitive performance during laboratory induced cognitive stress

Abstract: The aim of this study was to examine the effect of 10 minutes of heart rate variability (HRV) biofeedback on cognitive performance and affect scores during induced stress. Eighteen healthy male volunteers (aged 23-41 years) exposed to workrelated stress, were randomised into an HRV biofeedback intervention (BIO) and a comparative intervention group (COM). Subjects completed a modified Stroop task, which included having to mentally count 18 white squares randomly presented between colour words, before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
107
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(117 citation statements)
references
References 39 publications
7
107
3
Order By: Relevance
“…Specifically, these findings suggest that interventions that help patients gain control over their physiological arousal during moments of acute NA could potentially reap far greater health benefits than those primarily focused on decreasing NA in general. There are already several interventions that aim to teach patients to better regulate their physiological arousal during moments of acute NA and stress, such as HRV biofeedback (4951) and mindfulness-based interventions (52). However, applying these principles in situ can prove challenging (53).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these findings suggest that interventions that help patients gain control over their physiological arousal during moments of acute NA could potentially reap far greater health benefits than those primarily focused on decreasing NA in general. There are already several interventions that aim to teach patients to better regulate their physiological arousal during moments of acute NA and stress, such as HRV biofeedback (4951) and mindfulness-based interventions (52). However, applying these principles in situ can prove challenging (53).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Kim et al (2013) found brief HRV BFB training with recommended practice >10 weeks improved emotion and cognitive regulation in individuals with severe, chronic brain injury, while Prinsloo et al (2011) showed a single session of HRV BFB training improved cognitive performance in healthy adults during a modified stress inducing Stroop task. Four to five sessions of HRV BFB training, plus practice, has also been shown to reduce performance anxiety and improve subjective performance in classical musicians (Thurber, Bodenhamer-Davis, Johnson, Chesky, & Chandler, 2010).…”
Section: Hrv Bfb An Overviewmentioning
confidence: 99%
“…Related to the latter, all of the studies that we reviewed tested the impact of either a single BFB (Prinsloo et al 2011(Prinsloo et al , 2013 or NFB session or the impact of multiple BFB (Sutarto et al 2010(Sutarto et al , 2012(Sutarto et al , 2013 or NFB training sessions maximal 1 week after the last BFB session (i.e., Sutarto et al 2010). There is thus an important gap in this research domain with regard to potential long-term effects of both HRVand NFB training.…”
Section: Discussionmentioning
confidence: 99%
“…Within the domain of BFB, single training sessions showed to yield profit for attentional processes (Prinsloo et al 2013) and acute cognitive performance (Prinsloo et al 2011(Prinsloo et al , 2013 in comparison to a control group. Also, multiple BFB training sessions brought forth significant improvements in memory, decision and concentration tasks (Sutarto et al 2010), and cognitive performance (Sutarto et al 2012(Sutarto et al , 2013 in relation to a control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation